2004
DOI: 10.1016/j.matpur.2004.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic profiles of solutions to viscous Hamilton–Jacobi equations

Abstract: The large time behavior of solutions to the Cauchy problem for the viscous Hamilton-Jacobi equation u t − ∆u + |∇u| q = 0 is classified. If q > q c := (N + 2)/(N + 1), it is shown that non-negative solutions corresponding to integrable initial data converge in W 1,p (R N ) as t → ∞ toward a multiple of the fundamental solution for the heat equation for every p ∈ [1, ∞] (diffusion-dominated case). On the other hand, if 1 < q < q c , the large time asymptotics is given by the very singular self-similar solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 21 publications
1
57
0
1
Order By: Relevance
“…[11]. The pattern that we see after the corresponding renormalization, F q (y), is a modification of the Gaussian profile corresponding to the Very Singular Solution and changes with q.…”
Section: The Case Of Linear Diffusionmentioning
confidence: 74%
See 2 more Smart Citations
“…[11]. The pattern that we see after the corresponding renormalization, F q (y), is a modification of the Gaussian profile corresponding to the Very Singular Solution and changes with q.…”
Section: The Case Of Linear Diffusionmentioning
confidence: 74%
“…Assertions (10), (11), and (12) (13) for u(t) ∞ and ∇u(t) ∞ follow then from that for u(t) 1 by (11) with s = t/2. …”
Section: Preliminaries and Main Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The equation (1.1) has been studied by various authors for different values of the parameters p 2 and q > 1 as a model of linear or nonlinear diffusion with gradient-dependent absorption: see [8,9,11,12,15] for the semilinear case p = 2, and [1,7,16,20] for the quasilinear case p > 2. It has been shown that the large-time behaviour of this initial-value problem depends on the relative influence of the diffusion and absorption terms and leads to a classification into the following ranges of q:…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…As a matter of fact, if q > q ⋆ it is shown in [3,13] that the nonlinear term |∇u| q becomes negligible for large times, and that the solution of (1) behaves as t → ∞ like the self-similar solution I ∞ g of the linear heat equation, where g(t, x) = 1 t N/2 G x t 1/2 and G(ξ) = 1 (4π) N/2 exp − |ξ| 2 …”
Section: Introductionmentioning
confidence: 96%